Analisis Pengukuran Kinerja Instansi dengan Pendekatan Balanced Scorecard Pada Puskesmas X Kabupaten Bekasi - Muslimah Ayu Anggraini; Fahriza Nurul Azizah; Agustian Suseno (Universitas Indraprasta PGRI Jakarta, 2022)
This study aims to determine how the performance of Puskesmas X Kabupaten Bekasi is measured using a balanced scorecard approach. Balanced scorecard is a comprehensive performance measurement technique by measuring organizational performance based on financial aspects and non-financial aspects using 4 perspectives, finance, customer, internal business processes, learning and growth. The research method used is a descriptive method with a quantitative approach from observations, questionnaires, interviews, and documentation. The results showed that the financial perspective, namely the economic ratio and efficiency ratio were categorized as good, while the effectiveness ratio was categorized as not good. From the customer's perspective, it shows a good level of patient satisfaction, the ability to retain old patients is good while acquiring new patients is considered not good. From the perspective of internal business processes as measured by aspects of equipment, infrastructure, and processes, it shows good performance. The growth and learning perspective of employee satisfaction and employee productivity shows good performance results. Thus, overall viewed from the four perspectives of the balanced scorecard, the performance of the Puskesmas has achieved good results.